Awarding PhD Powers to Polytechnics: An Academic Trap? - Brás, Gonçalo Rodrigues (2021)
The aim of this article is to understand whether the conditions in Portuguese public polytechnics (PPPs) when studying for a PhD are similar to those in Portuguese public universities (PPUs). Three pillars were analyzed (research, academic staff degree, and precarious rate of academic staff), and to this end, we conducted independent sample t-tests and designed a correlation matrix to shed light on the relationship between the percentage of precarious academic staff and the shortrun variables in the environment of PPPs. The main findings reveal differences between PPUs and PPPs, indicating that policymakers failed to ensure that PPPs are competitive vis-a-vis PPUs in this area. Decree-Law No. 65/2018 granting PPPs the right to award doctoral degrees gives rise to a number of risks: a loss of focus in PPPs, the disappearance of the most used system in higher education (binary or dual system), and the absence of higher institutions in Portugal that provide practical training. If this is the path chosen by policymakers and the nature of course programs in PPPs and PPUs are becoming more similar, we strongly recommend that similar conditions should prevail in the two subsystems; this entails greater investment in PPPs and even the possibility of awarding PhD professional degrees in close connection with firms and corporations.